UNC-52/perlecan isoform diversity and function in Caenorhabditis elegans. (May 2001) - Rogalski, T. M.; Mullen, G. P.; Bush, J. A.; Gilchrist, E. J.; Moerman, D. G.
Abstract : The unc-52 gene encodes the nematode homologue of mammalian perlecan, the major heparan sulphate proteoglycan of the extracellular matrix. This is a large complex protein with regions similar to low-density lipoprotein receptors, laminin and neural cell-adhesion molecules. Three major classes of UNC-52/perlecan isoforms are produced through alternative splicing, and these distinct proteins exhibit complex spatial and temporal expression patterns throughout development. The unc-52 gene plays an essential role in myofilament assembly in body-wall muscle during embryonic development.